URGENSI MOTIVASI DALAM PROSES PEMBELAJARAN - Rumhadi, Tri (Balai Diklat Keagamaan Surabaya, 2017)
Motivation factors play an important role in influencinglearning. Motivation plays a very important role in humanefforts to achieve the desired goals, in the field of educationand other purposes.Motivation is impetus, it means there is a conscious effort toinfluence one’s behavior to move his heart to act to dosomething to achieve certain results or goals Purwanto (1996:71). With the motivation learners can develop activities andinitiatives that is able to direct and maintain persistence inlearning activities. There are several forms and ways to fostermotivation in school activities such as gift giving, score, praise,punishment, competition, repetition, and interest.